Covalent targeting of remote cysteine residues to develop CDK12 and 13 inhibitors - Bullock, A; Elkins, J; Dixon-Clarke, S; Zhang, T; Kwiatkowski, N; Olson, C; Abraham, B; Greifenberg, A; Ficarro, S; Liang, Y; Hannett, N; Manz, T; et al. (Nature Publishing Group, 2016)
Cyclin-dependent kinases 12 and 13 (CDK12 and CDK13) play critical roles in the regulation of gene transcription. However, the absence of CDK12 and CDK13 inhibitors has hindered the ability to investigate the consequences of their inhibition in healthy cells and cancer cells. Here we describe the rational design of a first-in-class CDK12 and CDK13 covalent inhibitor, THZ531. Co-crystallization of THZ531 with CDK12–cyclin K indicates that THZ531 irreversibly targets a cysteine located outside the kinase domain. THZ531 causes a loss of gene expression with concurrent loss of elongating and hyperphosphorylated RNA polymerase II. In particular, THZ531 substantially decreases the expression of DNA damage response genes and key super-enhancer-associated transcription factor genes. Coincident with transcriptional perturbation, THZ531 dramatically induced apoptotic cell death. Small molecules capable of specifically targeting CDK12 and CDK13 may thus help identify cancer subtypes that are particularly dependent on their kinase activities.